Highly Efficient Photocatalyst Fabricated from the Chemical Recycling of Iron Waste and Natural Zeolite for Super Dye Degradation - Fatma Mohamed; Safwat Hassaballa; Mohamed Shaban; Ashour M. Ahmed (Nanomaterials, 2022)
In this paper, Fe2O3 and Fe2O3-zeolite nanopowders are prepared by chemical precipitation utilizing the rusted iron waste and natural zeolite. In addition to the nanomorphologies; the chemical composition, structural parameters, and optical properties are examined using many techniques. The Fe2O3-zeolite photocatalyst showed smaller sizes and higher light absorption in visible light than Fe2O3. Both Fe2O3 and Fe2O3-zeolite are used as photocatalysts for methylene blue (MB) photodegradation under solar light. The effects of the contact time, starting MB concentration, Fe2O3-zeolite dose, and pH value on photocatalytic performance are investigated. The full photocatalytic degradation of MB dye (10 mg/L) is achieved using 75 mg of Fe2O3-zeolite under visible light after 30 s, which, to the best of our knowledge, is the highest performance yet for Fe2O3-based photocatalysts. This photocatalyst has also shown remarkable stability and recyclability. The kinetics and mechanisms of the photocatalytic process are studied. Therefore, the current work can be applied industrially as a cost-effective method for eliminating the harmful MB dye from wastewater and recycling the rusted iron wires.